2009
DOI: 10.1002/fut.20402
|View full text |Cite
|
Sign up to set email alerts
|

Corporate usage of financial derivatives, information asymmetry, and insider trading

Abstract: This article investigates whether financial derivative usage by Australian corporations constitutes information asymmetry when proxied by profitable trading in the firms' securities by insiders. The findings show that insiders who trade in companies that employ derivatives make larger purchase returns compared to insiders in nonuser firms with regard to trading identity, trading intensity, variability of usage, volume of trading, and industry effects. A plausible explanation is that asymmetry is driven by deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“… The level of ex‐ante exposure and the firm's corresponding hedging programme was argued by Nguyen, Faff and Hodgson () to be a source of private information. They reported that insiders in firms that use derivatives earn a higher abnormal return as compared to firms that do not employ financial derivatives. …”
mentioning
confidence: 99%
“… The level of ex‐ante exposure and the firm's corresponding hedging programme was argued by Nguyen, Faff and Hodgson () to be a source of private information. They reported that insiders in firms that use derivatives earn a higher abnormal return as compared to firms that do not employ financial derivatives. …”
mentioning
confidence: 99%
“…For example, Frankel and Li () use the profitability of insider trades to measure the information asymmetry between insiders and outsiders. Nguyen et al () proxy information asymmetry by the profits generated from insiders’ transactions. Joseph and Wintoki () study the information advantage of insiders by investigating the profits from their transactions.…”
Section: Methodsmentioning
confidence: 99%
“…A respeito do que foi citado até o momento -em geral, há uma maior utilização de derivativos para proteção, do que para especulação -é lógico pensar que o impacto da utilização dos mesmos seja positivo, tendo em vista que o hedge visa proteger as companhias de impactos (negativos ou positivos) em suas operações, reduzindo suas incertezas e exposições relacionadas as fricções de mercado (DEMARZO;DUFFIE, 1995;BROWN, 2001;DADALT;NAM, 2002;ARETZ;BARTRAM, 2010;MAGNANI, 2017). De forma geral isso é observado em grande parte dos estudos analisados, embora tenham estudos em que não é possível afirmar que houve um ganho ao utilizar derivativos financeiros para hedge (CLARK;JUDGE;MEFTEH, 2006;JIN;JORION, 2006;MACHADO, 2007;SMITH, 2007;NGUYEN;FAFF;HODGSON, 2010).…”
Section: Revisão Da Literaturaunclassified